Sign Code In Guiding The Ratoh Jaroe Dance On The Deaf Dancer Kembang Renjana - Fadma Wahyu Rositasari; Sekti, Retnayu Prasetyanti (Solah, 2025)
Dance coaches in dance training for deaf children act as guides by using hand signals to help students understand the flow and tempo of the dance. The purpose of this research is describes the signal code carried out by the motion guide in the performance of the Ratoh Jaroe dance at the Deaf Kembang Renjana Dance Team at SLB-B Karya Mulia Surabaya. The research approach uses a qualitative research approach, data collection techniques on field observation, interview, and documentation. The result of research data collection are described in the form of descriptive analysis. The research results, describe that the use of sign code as a visual symbol as a way to imitate movement visually. This is a real manifestation of the implementation of total communication, which allows deaf students to understand instruction and express dance movements without barriers to verbal communication. The addition of this technique aims to ensure that learning materials can be conveyed more effectively and thoroughly. Keywords: Signal Code, Dance Motion Guide